Specialist community teams for adults with learning disabilities: referrals to a countywide service in England. Issue 2 (1st April 2019) - Clare, Isabel C.H.; Wade, Kelly A.; Ranke, Nadine; Whitson, Sarah; Lillywhite, Alison; Jones, Elizabeth; Broughton, SallyAnne; Wagner, Adam; Holland, Anthony J.
Abstract : Purpose: While "generic" community teams for adults with learning disabilities (CTs) are well-established in the UK, very little recent evidence is available about any aspect of their work. As part of a larger project about the role, structure and functioning of CTs, the purpose of this paper is to provide data about referrals. Design/methodology/approach: Over three months, the authors obtained data about 270 consecutive new referrals to five CTs in a countywide integrated health (NHS) and care management (local authority) service. Findings: The 270 referrals related to 255 individuals, mainly already service users, with almost a third (30 per cent, n =204) described as people with severe or profound disabilities. Consistent with the reported living arrangements (residential accommodation or with one or more family members (87 per cent, n =270)), referrals were most often made by social care staff, General Practitioners or carers. The referrals related to a wide range of issues including mental health and/or behavioural needs, physical health and skills, and independence. The major group, however, were requests about a person's entitlement to specialist learning disability services and/or reviews of an existing social care package. Research limitations/implications: The focus on new referrals and the exclusion of intra-team referrals mean that the data are not representative of a CT's caseload and cannot be used as a basis for resourcing. Nevertheless, the findings emphasise the heterogeneity of the population, and the long-term and varied nature of their needs, meaning that CTs require access to a range of expertise and, often, an inter-agency approach. The implications for service design are considered. Originality/value: This is the first empirical study of referrals to specialist integrated (health and care management) community learning disabilities teams in England.